(untitled) (ARQUISUR Revista, 2024)
This paper proposes to argue for the hypothesis of the constitutive role of dispossessions in the urbanization of society. The approach is based on Lefebvre’s (1999) conception of the urban phenomenon and his understanding of the critical zone, which precedes the industrial city on the temporal and spatial axis towards the complete urbanization of society. The article poses that the evictions of self-produced urban occupations express the dialectically interrelated moments of implosion-explosion urbanization. Eviction processes are globally connected, which responds to the demands of financialized capital for land bank accumulation and occurs by justifying narratives that legitimize the logic of the commodity. A dialectical relationship of violence and necessity is established between urban occupations of peripheral territories and the capital in real estate finance, which contextualizes the violent acts of dispossession as a search for domination over the collective power of occupations.